What Drives Muslim Tourists' Visit Intention? The Roles of Halal Assurance, Service Quality, and Brand Trust in Muslim-Friendly Restaurants - Keyshifa Anardi; Bethani Suryawardani; Rahmat Hidayat (Journal of Digital Marketing and Communication, 2026)
The rise in halal travel drove an increasing demand for Muslim-friendly restaurants capable of meeting Muslim tourists' needs through halal certification and high-quality service. This study examined the effects of Halal Assurance and Service Quality on Visit Intention, with Brand Trust serving as a mediating variable, among Muslim-friendly restaurants in the Braga area of Bandung. A quantitative approach was employed involving 207 respondents selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicated that Halal Assurance and Service Quality had positive and significant effects on both Brand Trust and Visit Intention. However, Brand Trust did not have a significant effect on Visit Intention and, therefore, did not mediate the relationships between Halal Assurance, Service Quality, and Visit Intention. These findings suggested that Muslim tourists placed greater emphasis on halal assurance and service quality than on brand trust when determining their intention to visit Muslim-friendly restaurants.